Handbook of poststack seismic attributes - Barnes, Arthur E. (Society of Exploration Geophysicists, 2016)
The Handbook of Poststack Seismic Attributes (SEG Geophysical References Series No. 21) is a general reference for poststack seismic attributes. It discusses their theory, meaning, computation, and application, with the goal of improving understanding so that seismic attributes can be applied more effectively. The chapters of the book build upon each other and progress from basic attributes to more involved methods. The book introduces the ideas that underlie seismic attributes and reviews their history from their origins to current developments. It examines attribute maps and interval statistics; complex trace attributes; 3D attributes that quantify aspects of geologic structure and stratigraphy, primarily dip, azimuth, curvature, reflection spacing, and parallelism; seismic discontinuity attributes derived through variances or differences; spectral decomposition, thin-bed analysis, and waveform classification; the two poststack methods that purportedly record rock properties -- relative acoustic impedance through recursive inversion, and Q estimation through spectral ratioing; and multiattribute analysis through volume blending, cross-plotting, principal component analysis, and unsupervised classification. The book ends with an overview of how seismic attributes aid data interpretation and discusses bright spots, frequency shadows, faults, channels, diapirs, and data reconnaissance. A glossary provides definitions of seismic attributes and methods, and appendices provide background mathematics. The book is intended for reflection seismologists engaged in petroleum exploration, including seismic data interpreters, data processors, researchers, and students.
SEG Digital Library"--Website.
Title from PDF title page (SEG eBooks Website, viewed November 1, 2016).
Keywords: Seismic prospecting.; Seismic reflection method.; elektronické knihy; electronic books